Epidural Analgesia With Surgical Stabilization of Flail Chest Following Blunt Thoracic Trauma in Patients With Multiple Trauma - Golic, Darko Aleksa; Svraka, Dragan; Keleman, Nataša; Petrovic, Snjezana (Frontiers in Medicine, 2018)
Flail chest, often defined as the fracture of three or more ribs in two or more places, represents the most severe form of rib fractures. Conservative treatment, consisting of respiratory assistance with endotracheal intubation and mechanical ventilation (internal pneumatic stabilization) and pain control, are the current treatments of choice in the majority of patients with multiple rib fractures. However, the use of mechanical ventilation may create complications. In selected patients, operative fixation of fractured ribs within 72 h post injury may lead to better outcomes. We conducted a retrospective analysis of a series of nine cases of patients who developed flail chest after blunt trauma, and were treated with surgical osteofixation of the chest wall and postoperative epidural analgesia at the University Clinical Center of the Republic of Srpska during the period from January 2015 to December 2016. Two patients had trauma to the chest only, and the other patients had associated injuries to the head, abdomen, spine, and fractures of the pelvis and long bones. In the majority of patients (77.7%), surgical stabilization of the chest was performed on the second day following the injury, (mean, 2.33 days)and no later than 5 days after the injury. All patients received epidural analgesia with 0, 25% bupivacaine and 0, 01% morphine and intravenous multimodal analgesia, beginning 6 hours after thoracotomy. The average length of ICU stay was 14.7 days (range 2 -36), while the average number of days of mechanical ventilation was 8.1.The average duration of hospitalization was 25.4 days. Tracheotomy was performed in 33.3% of study patients. Mortality in the observed group was 44.4%. This study shows that surgical stabilization and epidural analgesia reduced ventilator support, shortened trauma intensive care unit stay, and reduced medical costsvs internal pneumatic stabilization. Keywords: thoracic epidural analgesia, blunt thoracic trauma, multimodal analgesia, operative fixation of ribs